Establishment of sex-specific reference intervals for automated haematology analyser-delivered research parameters in healthy Korean adults: a retrospective database review. Issue 10 (8th October 2020) - Jeon, Kibum; Kim, Miyoung; Han, Junhee; Lee, Jiwon; Lee, Jee-soo; Kim, Han-Sung; Kang, Hee Jung; Lee, Young Kyung
Abstract : Objectives: Automated haematology analysers measure various parameters of relevance to clinical research along with routine complete blood count (CBC)-related components. We aimed to establish ethnicity-specific and sex-specific reference intervals for 26 research-specific parameters as well as 18 routinely reported components using a large cohort of healthy Korean adults. The necessity of requiring separate sex-specific reference intervals for each parameter was also examined. Design: A retrospective database review. Setting: Single tertiary-care hospital of approximately 375 physicians and 530 nurses. Participants: This study included 1383 reference individuals (840 men and 543 women). Primary and secondary outcome measures: Following the Clinical and Laboratory Standards Institute guidelines for establishing reference intervals, routine CBCs as well as research parameters were measured using an ADVIA 2120i instrument. Results: All the routine components except for mean platelet volume and per cent lymphocytes differed significantly between men and women. Most research parameters also differed between the sexes; the exceptions were large platelets, platelet dry mass distribution width, per cent basophil saturation, per cent peroxidase saturation and per cent abnormal peroxidase absorption. Despite these differences, separate reference intervals for men and women were required only for two research-specific parameters: 'percentage high cellular haemoglobin' and 'percentage of hyperchromic red blood cells (RBCs)'. Conclusion: Even though most parameters showed significant differences between men and women, none of the evaluated parameters except two RBC-related factors required separate reference intervals for each sex.